Multicentric Castleman’s Disease, Associated with Idiopathic Thrombocytopenic Purpura - Ruchi Sood; Harris C. Taylor; Hamed Daw (Case Reports in Hematology)
The most common cause of a neck mass in young adults is hyperplastic lymphadenopathy consequent to infection and inflammation. Castleman’s disease (CD), an unusual benign lymphoproliferative disorder, infrequently causes neck masses. It occurs in unicentric (UCD) and multicentric (MCD) forms and is associated with human immunodeficiency virus (HIV), human herpes virus 8 (HHV-8), and Kaposi's sarcoma. We present the third known association between MCD and previous immune thrombocytopenia in the absence of HIV and HHV-8 infection and review its association with other autoimmune disorders and attendant implications for pathogenesis. Finally, we summarize the current approach to therapy.